Transcaval and Intracardiac Extension of Type A Thymoma and Myxoma: A Report of Two Rare Cases - Taghiyev, Zulfugar T.; Beier, Lili-Marie; Moustafine, Vadim; Bechtel, Matthias; Strauch, Justus T.; Boening, Andreas (The Thoracic and Cardiovascular Surgeon Reports, 2024)
We report two cases of rare invasive tumors presenting with transvenous and intracardiac extensions. In one instance, an unusual invasive thymoma type A penetrated into the heart chamber; the other case was an extension of a myxoma into the right atrium that was associated with superior vena cava syndrome. Our interest was stimulated by the rarity of these clinicopathological observations and the unusual clinical features of diagnostic and therapeutic methods presented by these cases.
Keywords: invasive thymoma; myxoma; intracardiac tumor